Faktor Penentu Daya Beli Masyarakat Berdasarkan Tingkat Inflasi, Tingkat Pendapatan Masyarakat, dan Harga Kebutuhan Pokok: Determinants of People's Purchasing Power Based on Inflation Rates, Income Levels, and Prices of Basic Necessities - Suci Ramadhani Isran; Inez Melati Sukma; Rossalina Utami Putri; Fakhira Amalia; Siti Ayu Agustin; Rudianto Rudianto (CV Warnak Johanna Nusantara, 2026)
Inflation is a macroeconomic indicator that has a direct impact on price stability and people's purchasing power. An increase in the prices of goods and services that is not matched by income growth has the potential to reduce household consumption. This study aims to analyze the effect of inflation rates, community income levels, and the prices of basic necessities on people's purchasing power, both partially and simultaneously. The research method used is a quantitative approach with a survey technique through the distribution of questionnaires to 100 respondents selected using simple random sampling. The data were analyzed using multiple linear regression with the help of IBM SPSS version 26. The types of tests carried out include validity, reliability, classical assumption, t-test, F-test, and coefficient of determination tests. The results show that partially, the inflation rate, community income level, and basic commodity prices have a positive and significant effect on people's purchasing power. Simultaneously, these three variables also have a significant effect with a contribution value of 52.4%. The basic commodity price variable has the most dominant effect on people's purchasing power.